Overview and Benchmarking of Motion Detection Methods (Background Modeling and Foreground Detection for Video Surveillance, 2015)
Motion detection is closely coupled with higher level inference tasks such as detection, localization, tracking, and classiﬁcation of moving objects, and is often considered to be a preprocessing step. Its importance can be gauged by the large number of algorithms that have been developed to-date and the even larger number of articles that have been published on this topic. A quick search for ”motion detection” on IEEE Xplore c© returns over 20,000 papers. This shows that motion detection is a fundamental topic for a wide range of video analytic applications. It also shows that the number of motion detection methods proposed so far is impressively large.